Ayahuasca-induced personal death experiences: prevalence, characteristics, and impact on attitudes toward death, life, and the environment - David, Jonathan; Bouso, José Carlos; Kohek, Maja; Ona, Genís; Tadmor, Nir; Arnon, Tal; Dor-Ziderman, Yair; Berkovich-Ohana, Aviva (Frontiers in Psychiatry, 2023)
Despite an emerging understanding regarding the pivotal mechanistic role of subjective experiences that unfold during acute psychedelic states, very little has been done in the direction of better characterizing such experiences and determining their long-term impact.The present paper utilizes two cross-sectional studies for spotlightingfor the first time in the literaturethe characteristics and outcomes of self-reported past experiences related to one's subjective sense of death during ayahuasca ceremonies, termed here Ayahuascainduced Personal Death (APD) experiences. Study 1 (n=54) reports the prevalence, demographics, intensity, and impact of APDs on attitudes toward death, explores whether APDs are related with psychopathology, and reveals their impact on environmental concerns.Study 2 is a larger study (n=306) aiming at generalizing the basic study 1 results regarding APD experience, and in addition, examining whether APDs is associated with self-reported coping strategies and values in life. Our results indicate that APDs occur to more than half of those participating in ayahuasca ceremonies, typically manifest as strong and transformative experiences, and are associated with an increased sense of transcending death (study 1), as well as the certainty in the continuation of consciousness after death (study 2). No associations were found between having undergone APD experiences and participants' demographics, personality type, and psychopathology. However, APDs were associated with increased self-reported environmental concern (study 1). These experiences also impact life in profound ways. APDs were found to be associated with increases in one's self-reported ability to cope with distress-causing life problems and the sense of fulfillment in life stemming from living according to one's values (study 2). The study's findings highlight the prevalence, safety and potency of death experiences that occur during ayahuasca ceremonies, marking them as possible mechanisms for psychedelics' long-term salutatory effects in nonclinical populations. Thus, the present results join other efforts of tracking and characterizing the profound subjective experiences that occur during acute psychedelic states.